DEFORMATION AND DESTRUCTION OF MATERIALS WITH SIGNIFICANT INTERNAL FRICTION - BAHRII, OLENA; DOROFIEIEV, OLEKSANDR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The problem of influence of compressive stresses on the patterns of deformation and destruction of these materials, which is important for a large class of machines and structures interacting with various "non-classical" materials, is considered.Based on the analysis of the results of numerous experimental studies by many scientists, it was concluded that the strength of most materials increases with an increase in the magnitude of all-round compressive stresses. This clearly indicates the manifestation of internal dry friction in the limit stage of deformation of such materials. Therefore, the strength criteria, or the criteria for the transition to the limit state of these materials, must consider the influence of not only the deviators of the stress tensor, but also the stress ratio.The influence of internal friction on the patterns of deformation in the range of "working" stresses is significantly manifested for discrete, granular and loose materials: concrete, soils, rocks, coal, grain, etc. The strength and shear deformations of these materials are significantly affected by the amount of compressive stresses. Therefore, they can be attributed to the class of materials with a significant manifestation of internal friction. The analysis of experimental data, conducted mainly with soils and loose materials, allows us to conclude that the determining physical dependences between stresses and strains of these materials should reflect not only the relationship between deviators of stresses and strains, but also between layer tensors. Dependencies of this type are used in nonlinear soil mechanics, but require clarification, theoretical and experimental justification.It is concluded that further theoretical and experimental studies of the patterns of deformation of materials with a significant manifestation of friction in the near-limit stage are necessary. This will make it possible to develop calculation models for solving the problems of interaction of machines with such materials.
Keywords: compressive stress; patterns of deformation, internal friction; discrete material